A framework for strategic river restoration in China. Issue 7 (9th November 2016) - Speed, Robert A.; Li, Yuanyuan; Tickner, David; Huang, Huojian; Naiman, Robert J.; Cao, Jianting; Lei, Gang; Yu, Lili; Sayers, Paul; Zhao, Zhongnan; Wei, Yu
ABSTRACT: In response to major water-related challenges, the Chinese government is preparing to significantly expand river restoration efforts. The high level of development in many Chinese river basins requires that this work be undertaken strategically. This article identifies current global challenges to river restoration and presents a framework for strategic river restoration, together with a set of eight 'golden rules'. The framework and rules were developed specifically to address the Chinese situation, but are relevant elsewhere, particularly for heavily developed and highly contested river basins.